Long-Term Follow-Up of Orthognathic Surgery in 19 Patients with Juvenile Idiopathic Arthritis - Henrik Krarup; Thomas Klit Pedersen; Paula Frid; Sven Erik Nørholt (Stilus Optimus, 2023)
Objectives: Dentofacial deformity following juvenile idiopathic arthritis with temporomandibular joint involvement is associated with functional, aesthetic, and psychosocial impairment. Surgical treatment may involve combinations of orthognathic surgery. The aims of this retrospective study were to assess orofacial symptoms, functional and aesthetic status, and stability after orthognathic surgery. Material and Methods: Nineteen patients with juvenile idiopathic arthritis of the temporomandibular joint (TMJ) and dentofacial deformities were included. All patients were treated with combinations of bilateral sagittal split osteotomy, Le Fort I and/or genioplasty, between September 10, 2007 and October 17, 2017. Analysis of patient symptoms and clinical registrations, and frontal/lateral cephalograms was performed pre- and postoperative and long-term (mean: 3.8 and 2.6 years, respectively). Results: Patients experienced no changes in orofacial symptoms or TMJ function, and stable normalisation of horizontal and vertical incisal relations at long-term (horizontal overbite; vertical overbite: P < 0.05). Mandibular lengthening was achieved postoperatively (from mean 79.7 to 87.2 mm; P = 0.004) and was stable. Sella-nasion to A point (SNA) and sella-nasion to B point (SNB) angles increased postoperatively (SNA, mean 79.9° to 82.8°; P = 0.022 and SNB, mean 73.9° to 77.8°; P = 0.003), however, largely reverted to preoperative status at long-term. Conclusions: Orthognathic surgery normalized incisal relations while providing stable mandibular lengthening without long-term deterioration of temporomandibular joint function or orofacial symptoms. No long-term effect on jaw advancements was observed.